TNFAIP3 and IL12B gene polymorphisms associated with psoriasis vulgaris in an Egyptian cohort. (18th November 2014) - Haase, O.; Mosaad, H.; Eldarouti, M.A.; Elramly, A.Z.; Samir, N.; Abdelhady, M.M.; Samir, M.; El‐Gharib, I.; Salah, S.; El‐Shennawy, F.A.; Mosaad, Y.; Elwan, N.; et al.
Abstract Background Psoriasis vulgaris is a common chronic inflammatory skin disease. Development of early onset psoriasis is, to some extent, genetically determined and a strong association with the major histocompatibility complex HLA‐Cw6 has been demonstrated. The use of genome‐wide association studies has highlighted novel genes associated with the development of psoriasis as IL12B, IL23R, TNFAIP3 and IL13 for instance. The majority of these studies were performed on cohorts of European descent. Objective To determine whether inter‐ethnic differences exist in the genetic susceptibility to psoriasis, we genotyped single‐nucleotide polymorphism variations in the vicinity of candidate genes in 132 Egyptian patients and 175 healthy controls. Methods Blood samples of patients and controls were screened for nucleotide polymorphisms in four candidate genes by TaqMan single‐nucleotide polymorphisms Genotyping Assays. Results We found a significant association between psoriasis and the single‐nucleotide polymorphism rs610604, within the TNFAIP3 gene. The TNFAIP3 gene is involved in the TNF‐α signalling cascade (P‐value: 0.004952), a key step in the pathogenesis of psoriasis. Although there was no significant association found between rs610604 (IL12B) and rs11209026 (IL23R) in this population, the interaction of these two genes showed a significant association with psoriasis (P‐value: 0.025). Moreover, when selecting the patients with early disease onset (less than 30 years), we also found that the association of IL12B and psoriasis was highly significant (P‐value 1.14 × 10−12). No association between rs20541 (IL13) and psoriasis was observed in our Egyptian cohort. Conclusion Replicating the association of single‐nucleotide polymorphisms in the TNFAIP3, IL12B and IL23R genes with psoriasis vulgaris, in subjects from different ethnic backgrounds, underlines their importance in the pathogenesis of the disease. In contrast, the lack of any association between rs20541 (IL13) and psoriasis in our Egyptian cohort suggests the existence of important inter‐ethnic genetic differences in psoriasis susceptibility.